2015
DOI: 10.1620/tjem.236.297
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-inflammation Index, Based on Platelet Counts and Neutrophil-Lymphocyte Ratio, Is Useful for Predicting Prognosis in Small Cell Lung Cancer

Abstract: Small cell lung cancer (SCLC) is an aggressive disease characterized by rapid growth and metastases. It has been recognized that the inflammation of the microenvironment plays a critical role in the development of malignancies. However, little is known about the role of multiple inflammatory and hematological markers in the prognosis of SCLC. The aim of this study was to determine the clinical significance of pre-treatment inflammation-based scores and characteristics as prognostic indicators for the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
252
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(268 citation statements)
references
References 39 publications
10
252
4
2
Order By: Relevance
“…Several studies have reported that a high PLR is a parameter that reflects systemic inflammatory response in numerous diseases [21,22]. A PLR increase has also been reported to be associated with cardiovascular complications and poor prognosis in malignancies [23,24]. The SII assesses 3 of the hemostatic system markers that participate in the inflammatory process at the same time: platelets, lymphocytes, and neutrophils [13,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that a high PLR is a parameter that reflects systemic inflammatory response in numerous diseases [21,22]. A PLR increase has also been reported to be associated with cardiovascular complications and poor prognosis in malignancies [23,24]. The SII assesses 3 of the hemostatic system markers that participate in the inflammatory process at the same time: platelets, lymphocytes, and neutrophils [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a combined marker of chronic inflammation, such as the SII, reflecting high neutrophils and platelets, and low lymphocytes, may contribute additional information regarding the inflammatory and immunological balance of the body. Interest in the SII has grown recently because it has been found to be predictive of the prognoses of patients with diverse oncological conditions [16,[23][24][25]. There is a strong linkage between obesity, cancer, inflammation, and clinical outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already identified pretherapeutic prognostic markers and scores to predict outcome in SCLC patients [7,8,9,10,11,12,13,14]. A recent study also demonstrated that pretreatment mGPS and PNI are independent predictors of OS in patients with advanced SCLC [14].…”
Section: Discussionmentioning
confidence: 99%
“…For about 30 years, lactate dehydrogenase (LDH) and serum albumin have been described to predict OS in SCLC [7,8,9]. Different markers and scores for acute inflammation, i.e., the neutrophil-to-lymphocyte ratio (NLR), C-reactive protein (CRP) levels, the modified Glasgow prognostic score (mGPS), the prognostic nutritional index (PNI), and the systemic immune-inflammation index (SII) have been associated with poor outcome in SCLC [10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…With regard to lung cancer, the prognostic significance of SII was reported for small cell lung cancer (9) and stage III NSCLC (10). However, to our knowledge, there are no previous studies that evaluated the significance of SII for resectable NSCLC.…”
mentioning
confidence: 99%